Study on retinol binding protein (RBP) receptor in hydatidiform mole trophoblastic cells (Medical Journal of Indonesia, 2007)
Hydatidiform mole is an abnormal pregnancy characterized by the proliferation of cytotrophoblastic, syncytiotrophoblastic, and intermediate trophoblastic cells in histological specimens. Vitamin A plays a role in controlling cell proliferation, and decrease in vitamin A level will cause an uncontrollable proliferation. To date, it is not known whether there is a relationship between vitamin A deficiency and hydatidiform mole. This study aimed to demonstrate the presence of retinol binding protein (RBP) receptors in the hydatidiform mole trophoblastic cells, that would provide explanation on the relationship of vitamin A and hydatidiform mole. The study was a descriptive study. The specimens of the study were paraffin blocks of hydatidiform mole made in 2005, and the examinations were performed by indirect immunohistochemistry. We examined the distribution of the cells showing expression of RBP receptor, the strength of expression, and location of the expression. As many as 21 specimens were collected, and the distributions of RBP receptor expression in hydatidiform mole trophoblastic cells ranged from moderate to dense. The expression in syncytiotrophoblastic cells was stronger than that in cytotrophoblastic cells. Furthermore, the expressions were found in the cell membranes and cytoplasm. (Med J Indones 2007; 16:146-50)